The phenomenology of pain in Parkinson’s disease - Camacho-Conde, José Antonio (Korean J Pain, 2020)
BACKGROUND: Parkinson’s disease (PD) is a neurodegenerative disorder that is the second most common disorder after Alzheimer’s disease. PD includes both “motor” and “non-motor” symptoms, one of which is pain. The aim of this study was to investigate the clinical characteristics of pain in patients with PD. METHODS: This cross-sectional study included 250 patients diagnosed with PD, 70% of which had mild to moderate PD (stages 2/3 of Hoehn and Yahr scale). The average age was 67.4 years, and the average duration since PD diagnosis was 7.1 years. Relevant data collected from PD patients were obtained from their personal medical history. RESULTS: The prevalence of pain was found to be high (82%), with most patients (79.2%) relating their pain to PD. Disease duration was correlated with the frequency of intense pain (R: 0.393; P < 0.05). PD pain is most frequently perceived as an electrical current (64%), and two pain varieties were most prevalent (2.60 ± 0.63). Our findings confirm links between pain, its evolution over time, its multi-modal character, the wide variety of symptoms of PD, and the female sex. CONCLUSIONS: Our results demonstrated that the pain felt by PD patients is mainly felt as an electrical current, which contrasts with other studies where the pain is described as burning and itching. Our classification is innovative because it is based on anatomy, whereas those of other authors were based on syndromes.